2005
DOI: 10.1111/j.1462-2920.2005.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses to antimicrobial agents in biofilms

Abstract: Bacterial biofilms demonstrate adaptive resistance in response to antimicrobial stress more effectively than corresponding planktonic populations. We propose here that, in biofilms, reaction-diffusion limited penetration may result in only low levels of antimicrobial exposure to deeper regions of the biofilm. Sheltered cells are then able to enter an adapted resistant state if the local time scale for adaptation is faster than that for disinfection. This mechanism is not available to a planktonic population. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
108
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 10 publications
(15 reference statements)
1
108
0
Order By: Relevance
“…Our results show that exponential-and stationary-phase planktonic cells of Z. mobilis were equally susceptible to benzaldehyde, indicating that benzaldehyde resistance was not growth rate dependent for planktonic cells. In general, increased resistance in biofilms may be a result of altered gene expression which leads to physiological and/or structural changes during biofilm formation (17,31,33,38). It is possible that the benzaldehyde resistance of Z. mobilis biofilms is conferred by, for example, benzaldehyde excretion or altered membrane composition to counteract any benzaldehyde effect on membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that exponential-and stationary-phase planktonic cells of Z. mobilis were equally susceptible to benzaldehyde, indicating that benzaldehyde resistance was not growth rate dependent for planktonic cells. In general, increased resistance in biofilms may be a result of altered gene expression which leads to physiological and/or structural changes during biofilm formation (17,31,33,38). It is possible that the benzaldehyde resistance of Z. mobilis biofilms is conferred by, for example, benzaldehyde excretion or altered membrane composition to counteract any benzaldehyde effect on membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in biofilms can differ profoundly in terms of phenotypic characteristics (31,33) or adaptive responses to stress (17,38) from their planktonic counterparts, which can provide survival advantages and protection in a range of environmental conditions (16,23). Biofilms are also commonly found on medical implants and are responsible for many persistent infections due to their increased resistance to antimicrobial agents (13).…”
mentioning
confidence: 99%
“…Bacteria with biofilms may have an increased resistance to antimicrobials, ambient pressure and the host immune system (Arciola et al, 2001;Costerton et al, 2003;Szomolay et al, 2005). In order to understand the relationship between biofilms and antimicrobial resistance in S. Pullorum, we assayed the ability of the isolates to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…O'Toole and Kolter reported that protein synthesis was required for initiation of biofilm formation in Pseudomonas fluorescens WCS365 (36). Treatment of chloramphenicol at the onset of biofilm formation might affect the protein synthesis or the activity of some regulatory proteins, which in turn would affect its biofilm development and produce induction cues for larval settlement, while after 10 h of development, those proteins that were required for presenting larval settlement induction might have already been synthesized (50), which in turn would maintain the biofilm's ability to induce larval settlement. The surface protein profiles of YP-grown P. spongiae and Pgrown P. spongiae before attachment and after 10 h of attachment were then further investigated.…”
mentioning
confidence: 99%